TGF-β1 Augments the Apical Membrane Abundance of Lemur Tyrosine Kinase 2 to Inhibit CFTR-Mediated Chloride Transport in Human Bronchial Epithelia - Cruz, Daniel F.; Mitash, Nilay; Farinha, Carlos M.; Swiatecka-Urban, Agnieszka (Frontiers in Cell and Developmental Biology, 2020)
The most common disease-causing mutation in the Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) gene, F508del, leads to cystic fibrosis (CF), by arresting CFTR processing and trafficking to the plasma membrane. The FDA-approved modulators partially restore CFTR function and slow down the progression of CF lung disease by increasing processing and delivery to the plasma membrane and improving activity of F508del-CFTR Cl- channels. However, the modulators do not correct compromised membrane stability of rescued F508del-CFTR. Transforming Growth Factor (TGF)-β1 is a well-established gene modifier of CF associated with worse lung disease in F508del-homozygous patients, by inhibiting CFTR biogenesis and blocking the functional rescue of F508del-CFTR. Lemur Tyrosine Kinase 2 (LMTK2) is a transmembrane protein localized at the apical and basolateral membrane domain of human bronchial epithelial cells. Phosphorylation of the apical membrane CFTR by LMTK2 triggers its endocytosis and reduces the abundance of membrane-associated CFTR, impairing the CFTR-mediated Cl- transport. We have previously shown that LMTK2 knockdown improves the pharmacologically-rescued F508del-CFTR abundance and function. Thus, reducing the LMTK2 recruitment to the plasma membrane may provide a useful strategy to potentiate the pharmacological rescue of F508del-CFTR. Here, we elucidate the mechanism of LMTK2 recruitment to the apical plasma membrane in polarized CFBE41o- cells. TGF-β1 increased LMTK2 abundance selectively at the apical membrane by accelerating its recycling in Rab11-positive vesicles without affecting LMTK2 mRNA levels, protein biosynthesis, or endocytosis. Our data suggest that controlling TGF-β1 signaling may attenuate recruitment of LMTK2 to the apical membrane thereby improving stability of pharmacologically rescued F508del-CFTR.